On Competitive Price Adjustment for a Storable Good and Abstention from Trade - Eden, Benjamin (Journal of Political Economy, 1983)
The public good aspect of information is used to account for periods in which the aggregate level of trade is low. It is shown that abstention from trade may occur when the uncertainty with respect to the market-clearing price (there is no auctioneer) gets large relative to the cost of getting information about it and relative to the cost of postponing transactions. In this case, all agents are aware of bilateral Pareto-improving trading opportunities, but these opportunities are not exploited.